VALIDASI METODE ANALISIS LOGAM SENG (Zn) SECARA SPEKTROFOTOMETRI SERAPAN ATOM SERTA LOGAM RAKSA (Hg) DENGAN MERCURY ANALYZER PADA KRIM KOSMETIKA - , ERNI WIJAYANTI; , Dr. Abdul Rohman, M.Si., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Cream is one of usually applied cosmetics. The presence of heavy metals added to cosmetic such as Zn and Hg can cause risks if over the allowed concentration. This study is to validate the mehod analysis of atomic absorption spectrofotometry for Zn determination and mercury analyzer for mercury determination. Validation of method anaylisis is according to International Conference on Harmonization term by assesing several parameter figures namely linearity, sensitivity, precision and accuration. Cream samples are destructed by wet digestion using nitric acid-perchlorat mixture (1 : 1 v/v), then analyzed with atomic absorption spectrofotometry for Zn and mercury analyzer for Hg. The method analysis linearity obtained over 0,99 for correlation coefficient (r) and 0,995 for determination coefficient (r2) . Limit of detection obtained were 2,8614 Î¼g/g for Zn and 0,4749 Î¼g/kg. Limit of quantitation obtained were 9,5281 Î¼g/g for Zn and 1,5827 Î¼g/kg for Hg. Relative standard deviation used to determinate repeatability and interday precision obtained were on the allowed values of Horwitz and AOAC PVM. Accuration value obtained by assesing percent recovery were also on the allowed values of AOAC PVM. This validated method then applied to determine Zn and Hg concentration in some cream cosmetics. The level concentration of Zn and Hg obtained was below the allowed maximum concentration.